Electric Vehicle Mobility-as-a-Service: Exploring the "Tri-Opt" of Novel Private Transport Business Models. Issue 1 (2nd January 2019) - Cooper, Peter; Tryfonas, Theo; Crick, Tom; Marsh, Alex
ABSTRACT: Three distinct trends have emerged that have disrupted the dominance of privately owned, combustion-powered car transport in the United Kingdom. First, the electric powertrain has emerged as an affordable means of transport, addressing various existing environmental concerns; second, new models of car ownership are developing, particularly in urban areas; third, the growth of "smart city" thinking emphasizes capitalizing on increased connectivity and data availability to create value. We define the combination of these three trends as the "tri-opt" of private transport—three disruptors that should not be considered in isolation but as interacting, an inflection of the "Energy Trilemma." This paper applies systems thinking and a mixed methodology of workshops, interviews, and systems modeling to the UK city of Bristol's Smart EV Transport Hub project to identify concepts that positively combine two or more of these three "opts." We demonstrate that there are many synergistic overlaps and that combinations potentially create significant value, with use cases that the current literature has explored the least are of the greatest perceived value. We thus recommend that public–private sector collaboration in private transport—particularly at the intersection of electric vehicles, smart cities, and mobility-as-a-service—is prioritized for further investigation.